Teacher’s Conceptions of Caring and Protective Teaching Elements in Rwamwanja Refugee Settlement Schools - Wacklin, Ville (fi=Turun yliopisto|en=University of Turku|, 2016)
The purpose of this study is to find out what conceptions Rwamwanja refugee settlement teachers have about caring teaching methods. The study was conducted by analysing the data gathered from semi-structured interviews. Twelve teachers were interviewed in four different refugee settlement schools. The main theory of this study is based on ethics of care research by Nel Noddings. In addition, the framework was developed by combining the theories of resilience and psychosocial support which are often employed in research concerning emergency contexts. This study uses qualitative content analysis to describe the conceptions of caring teachers have and protective teaching elements they employ. The results of this study show that many of the key elements of caring and protective teaching were present in teacher’s answers. For example, in their answers, the majority of the teachers pointed out the significance of using soft discipline. However, many teaching elements considered ideal in emergency contexts were missing. These missing methods include routines and flexibility which are considered essential for vulnerable children. The teachers’ levels of conceptual thinking varied remarkably depending on their language skills. The communication was limited to very basic and concrete language in some of the interviews due to lack of mutual understanding. This also raised a question about the level of understanding between refugee pupils and teachers since there is no strong common language between them. The results of this research call for further studies about the effect of caring teaching elements in growth of resilience in refugee children. Keywords: The ethics of care, resilience, psychosocial support, education in emergencies, refugees, education, protection.